PROBLEMS OF ROLLING THE PILGRIME HEAD AND WAYS OF THEIR SOLUTION. Message 2 - Стасевский, Станислав; Угрюмов, Юрий; Балакин, Валерий (SWorldJournal, 2020)
The main directions of solving the problems of rolling the pilger head on the free section of the mandrel are considered due to: the choice of a rational feed mode, reduction of the rear end of the sleeve before rolling the head to reduce the displacement